Application of modern methods in teaching the discipline "Animal Genetics" - Suprun, Iryna (Problems of Environmental Biotechnology, 2021)
When teaching the discipline "Animal Genetics" for students at different stages of teaching, such elements as computer technology and e-learning course for independent work, demonstration of animation fragments, use of presentations and reference notes in explanation, test control to identify the level of knowledge acquisition in the classroom are used.